Dataset of air velocity and temperature fields inside an insulated box equipped with phase change material under several operating conditions - Tanathep Leungtongkum; Denis Flick; Nattawut Chaomuang; Alain Denis; Onrawee Laguerre (My University, 2023)
This article contains a description of protocol to measure air velocity field (by Particle Image Velocimetry - PIV) and temperature field (by T-type thermocouples) in an insulated box equipped with Phase Change Material (PCM) of melting point 0 °C. The influence of various conditions was studied: i) PCM position (at sidewall and at top), ii) aspect ratio of the box (height/width ∼ 1 and 1.7), iii) ambient temperature (10 °C, 20 °C and 30 °C), iv) test product initial temperature (4 °C and 10 °C) and vi) spacing beneath the load (0 mm and 20 mm). This article is related to a published research paper, it provides the dataset of all experiments which can be useful for experimenter to understand the phenomena and for expert in numerical model to validate the developed model e.g., by Computational Fluid Dynamic.
Keywords: Thermocouple; Phase-change material; Pyrometer; Phase Change Materials Research